Effect of chiral 2-ethylhexyl side chains on chiroptical properties of the narrow bandgap conjugated polymers PCPDTBT and PCDTPT. Issue 8 (11th May 2016) - Fronk, Stephanie L.; Wang, Ming; Ford, Michael; Coughlin, Jessica; Mai, Cheng-Kang; Bazan, Guillermo C.
Abstract : PCPDTBT* and PCDTPT* containing chiral 2-ethylhexyl side chains were synthesized and their resulting chiroptical properties were studied. PCPDTBT* exhibits a stronger chiroptical response compared to PCDTPT*. Abstract : Two narrow bandgap conjugated polymers containing chiral 2-ethylhexyl side chains were synthesized: poly[(4, 4-bis(2-ethylhexyl)cyclopenta-[2, 1- b :3, 4- b ′]dithiophene)-2, 6-diyl- alt -(2, 1, 3-benzothiadiazole)-4, 7-diyl] (PCPDTBT*) and poly[(4, 4-bis(2-ethylhexyl)cyclopenta[2, 1- b :3, 4- b 0]dithiophene)-2, 6-diyl- alt -[1, 2, 5]-thiadiazolo[3, 4- c ]pyridine] (PCDTPT*). The presence of a chiral substituent provides a handle to study the geometry of interchain aggregates and/or the secondary structure of these conjugated polymers in solution and in thin films via circular dichroism (CD) spectroscopy, provided that the asymmetry in the side-chain is translated to the optically active conjugated backbone. CD signals are observed for PCPDTBT* and PCDTPT* in poor solvent systems, which indicate the presence of chiral ordering in the aggregates. PCPDTBT* shows greater chiral order than PCDTPT* based on their relative anisotropy factors. Additionally, GIWAXS analysis reveals that PCPDTBT* films are more ordered than what is observed for the same polymer containing racemic 2-ethylhexyl chains. Upon solution deposition, the chiral ordering is found to translate to the solid-state microstructure for PCPDTBT* but not PCDTPT*. The presence of a pyridyl nitrogen on the thiadiazolo[3, 4- c ]pyridine ring of PCDTPT* favors a planar conformation for the backbone such that it has a higher rotational barrier compared to PCPDTBT*. This larger rotational barrier appears to limit the ability of PCDTPT* to adopt a helical structure or relevant chain distortions for achieving chiral aggregates.